Implementasi Kawasan Tanpa Rokok di Sekolah Menengah Atas Swasta Wilayah Perkotaan - Sari, Desi Nabila; Nafisah, Lu'lu; Intiasari, Arih Diyaning (Jurnal Kesehatan, 2023)
The large number of smokers in Indonesia needs coordinated and integrated action to address, especially since the number of smokers among students continues to rise. One of the measures to address this issue is the no smoking area policy, including at school. However, no smoking area policy objectives must be supported by optimum policy execution. This study aims to determine the implementation of the Non-Smoking Area Policy at Pramita High School Tangerang City. This study uses qualitative research by conducting in-depth interviews. The principal, students, and counseling teachers are the three primary informants. Teachers and administrative personnel serve as the two supporting informants. The Content Analysis approach was used to analyze the data. Non-Smoking Areas Policy has yet to be implemented optimally at SMA Pramita Tangerang City. The school needs more resources and has yet to constitute a working group to enforce a smoke-free zone and consequences for breaches. There have also been no reporting systems for breaches of this policy, making it impossible to determine the number of violations and the level of compliance of school residents with this policy of no-smoking areas. A school must strengthen the implementation of No Smoking Areas by conducting socialization, developing a dedicated team, providing supporting facilities and infrastructure and imposing strict punishments on violators of the restrictions.